Long shot [videorecording (Blu-Ray + DVD)] - Levine, Jonathan, 1976-; Theron, Charlize; Theron, Charlize; Rogen, Seth, 1982-; Rogen, Seth, 1982-; Raphael, June Diane (Lionsgate, 2019)
A New York journalist gets hired as a speechwriter for a presidential candidate who, as it turns out, was his babysitter and secret love interest during his teenage years.